encontre o produto dos coeficientes da equação (x-1)(x-2)(x+6)=0
gostaria do produto dos coeficientes
Soluções para a tarefa
Respondido por
0
(x - 1)(x - 2)(x - 6) = 0
x2 + 2x - x + 2 (x - 6) = 0
x^2 + x + 2 (x - 6) = 0
x^3 + x^2 + 2x - 6x^2 - 6x - 12
x^3 - 5x^2 - 4x - 12
x2 + 2x - x + 2 (x - 6) = 0
x^2 + x + 2 (x - 6) = 0
x^3 + x^2 + 2x - 6x^2 - 6x - 12
x^3 - 5x^2 - 4x - 12
Perguntas interessantes
Lógica,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Saúde,
1 ano atrás
Filosofia,
1 ano atrás